Terrestrial arthropod reviews (Brill, 2008)
Journal contains concise review articles on living and extinct insects, arachnids, and their relatives that use land during (a part of) their life history. The journal welcomes integrative reports on findings within a certain habitat or organism, but beyond the taxonomic description. Reports on species-species or species-environment interactions as well as biodiversity, conservation biology and the effect on habitats of ecological changes are especially welcome. New species descriptions, taxonomic revisions, or new records are specifically excluded.